W-Stability of Multistable Nonlinear Discrete-Time Systems - Zhishuai Ding; Guifang Cheng; Xiaowu Mu (Discrete Dynamics in Nature and Society)
Motivated by the importance and application of discrete dynamical systems, this paper presents a new Lyapunov characterization which is an extension of conventional Lyapunov characterization for multistable discrete-time nonlinear systems. Based on a new type stability notion of W-stability introduced by D. Efimov, the estimates of solution and the Lyapunov stability theorem and converse theorem are proposed for multi-stable discrete-time nonlinear systems.